PENGARUH PENDAPATAN TERHADAP KONSUMSI MELALUI MENTAL ACCOUNTING PADA MASYARAKAT DESA TUTUARU PULAU LETTI KABUPATEN MALUKU BARAT DAYA - Leunupun, Engrith Grafelia (Komunitas Manajemen Kompetitif, 2023)
This writing aims to empirically determine the relationship between income and consumption through mental accounting. This research was conducted by taking samples from the Tutuaru village community, Letti Island, Southwest Maluku Regency. The number of samples selected was 43, the samples were selected randomly based on anyone who could be found at the time of data collection. The results of the study are that income has a significant effect on the level of public consumption, while simultaneously mental accounting cannot influence income on consumption by the people of Tuturu Village.